2016
DOI: 10.7202/1037090ar
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Social Workers, Foreign Credential Recognition and Securing Employment in Canada

Abstract: Canada is a culturally diverse receiving country for transnational migration, and social workers are among the professional migrants who arrive in Canada each year. This article draws on findings from a four-year, grounded theory study on the professional adaptation processes and experiences of migrant social workers (n = 66) in the Canadian context. Study findings highlight a range of internal (personal) attributes and external (contextual) elements that interact to serve as either protective or vulnerabilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…There is now an extensive literature on the increasing mobility of social workers in Aotearoa New Zealand, as noted earlier, and in the United Kingdom (Hanna & Lyons, 2014;Hatzidimitriadou & Psoinos, 2017;Hussein, 2014;Hussein et al, 2011;Moriarty, Hussein, Manthorpe, & Stevens, 2012;Tinarwo, 2015;Zanca & Misca, 2016); Ireland (Walsh, Wilson, & O'Connor, 2010); Australia (Harrison, 2013;Papadopoulos, 2017Papadopoulos, 2018Zubrzycki, Thomson, & Trevithick, 2008;Modderman, Threlkeld, & McPherson, 2017); Canada (Brown, Sansfaçon, Éthier, & Fulton, 2014;Fulton, Pullen Sansfaçon, Brown, Éthier, & Graham, 2016;Pullen Sansfaçon, Brown, Graham, & Dumais Michaud, 2013). More recently, research has been published that has reported on the experiences of migrant workers in the United States (Lin, Chiang, Lux, & Lin, 2018), Zimbabwean social workers in South Africa (Mangena & Warria, 2017) and of Latin American social workers in Switzerland (Bolzman, 2015).…”
Section: Literaturementioning
confidence: 86%
See 1 more Smart Citation
“…There is now an extensive literature on the increasing mobility of social workers in Aotearoa New Zealand, as noted earlier, and in the United Kingdom (Hanna & Lyons, 2014;Hatzidimitriadou & Psoinos, 2017;Hussein, 2014;Hussein et al, 2011;Moriarty, Hussein, Manthorpe, & Stevens, 2012;Tinarwo, 2015;Zanca & Misca, 2016); Ireland (Walsh, Wilson, & O'Connor, 2010); Australia (Harrison, 2013;Papadopoulos, 2017Papadopoulos, 2018Zubrzycki, Thomson, & Trevithick, 2008;Modderman, Threlkeld, & McPherson, 2017); Canada (Brown, Sansfaçon, Éthier, & Fulton, 2014;Fulton, Pullen Sansfaçon, Brown, Éthier, & Graham, 2016;Pullen Sansfaçon, Brown, Graham, & Dumais Michaud, 2013). More recently, research has been published that has reported on the experiences of migrant workers in the United States (Lin, Chiang, Lux, & Lin, 2018), Zimbabwean social workers in South Africa (Mangena & Warria, 2017) and of Latin American social workers in Switzerland (Bolzman, 2015).…”
Section: Literaturementioning
confidence: 86%
“…First, many have experienced a degree of professional dislocation and discrimination (Fouché, Beddoe, Bartley, de Haan, 2013;Fouché, Beddoe, Bartley, & Parkes 2013;Hatzidimitriadou & Psoinos, 2017), sometimes to the extent that they face challenges in finding meaningful employment commensurate with their skills. Secondly, they may find gaining registration or licensing involves them in protracted communications over the recognition of their professional qualifications (Fouché, Beddoe, Bartley, de Haan, 2013;Fouché, Beddoe, Bartley, & Parkes 2013;Brown et al, 2014;Fulton et al, 2016;Papadopoulos, 2017Papadopoulos, , 2018. Thirdly, they too, often experience a very limited programme of transition (induction) in their new professional contexts, in comparison to those offered to members of other professions (Brown et al, 2014;Peter, Bartley, & Beddoe, 2017).…”
Section: Literaturementioning
confidence: 99%
“…The challenge for all newcomers, including youth, is to convince Canadian educational institutions and employers that they have the claimed credentials and that they are on par with those of Canadians. Foreign work credentials are assessed by various regulatory bodies depending on the profession (Fulton, Pullen-Sansfaçon, Brown, Éthier, & Graham, 2016). Credentials are evaluated based on their relevancy for Canadian society and the entry requirements for some professions (Houle & Yssaad, 2010).…”
Section: Transfer Of Foreign Credentialsmentioning
confidence: 99%
“…For work credentials, newcomers must first determine the licensing body and then produce documents while navigating language and cultural barriers. Fulton et al (2016) report, "Once engaged in the pursuit of foreign credential recognition, the participants encountered a myriad of external challenges including: bureaucratic red tape, difficulty obtaining required documentation from their countries of origin, and a lack of guidance and information about the credentialing process" (p. 74). Houle & Yssaad (2010) found that difficulties surrounding foreign credential recognition have detrimental effects for the labour market and for the societal engagement of newcomers in Canada.…”
Section: Transfer Of Foreign Credentialsmentioning
confidence: 99%
“…Evidence shows that there is duplication of tasks between the credential recognition and licensure processes, mixed messages within provincial regulatory bodies, and delays in obtaining licensure, resulting in frustrating challenges before being able to practice in Canada (Brown et al, 2018a). Furthermore, integrating into the workforce remains complicated, even after obtaining a license to practice (Fang, 2012; Fulton et al, 2016). Research in England and New Zealand mirror these findings of cumbersome bureaucratic processes (Bartley et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%